Potential Effect of Phlorotannins in Brown Algae for Antidiabetic Therapy: Molecular Docking Approach - Renagupita, Melani Sinastri; Rahadianto, Rahadianto; Garianto, Efyluk; Setianingsih, Herin (Makara Journal of Science, 2023)
This study aims to manifest the effect of the active compound phlorotannins in brown algae on decreasing insulin resistance by analyzing the predicted interaction between phlorotannins and protein tyrosine phosphatase 1B (PTP 1B) and estimating the pharmacokinetics and toxicity of the active compound for type 2 diabetes mellitus (DM) therapy. This type of research uses an in silico study to test the effect of using phlorotannins as an active compound in brown algae against PTP 1B inhibition. Starting from preparing materials, i.e., downloading the three-dimensional structure of phlorotannins via PubChem and PTP 1B via RSCB PDB (PDB 1A5Y), molecular docking using Molegro Virtual Docker 5, molecular visualization using PyMol and Discovery Studio, and predicting pharmacokinetics and toxicity via pkCSM have been conducted. Here, the phlorotannins include phloroglucinol, dioxinodehydroeckol, eckol, phlorofucofuroeckol-A, dieckol, 7-phloroeckol, and 6,6′-bieckol. In addition, Ertiprotafib and S-phosphocysteine are used here as the comparison controls for docking validation. All phlorotannins can bind to PTP 1B at the same binding site with drug control. Experimental results revealed that phlorotannins–PTP 1B produces lower energy than complex S-phosphocysteine–PTP 1B (−266.8 kJ/mol), which acts as a control here. However, phloroglucinol–PTP 1B produces (−208 kJ/mol) under the same condition. Compared with the drug control Ertiprotafib (−322.8 kJ/mol), the lower bond energy is owned by phlorofucofuroeckol-A (−370.6 kJ/mol), 7-phloroeckol (−328 kJ/mol), dieckol (−331.8 kJ/mol), and 6.6'-bieckol (−341 kJ/mol). Furthermore, phlorotannins are very well absorbed in the intestine. According to Lipinski’s rule, active compounds, such as phloroglucinol, eckol, and dioxinodehydroeckol have high potential as a drug. Phlorotannins are nontoxic against hepatocytes and have fewer side effects than drug control. Based on the obtained data, use of the active compound phlorotannins in brown algae can decrease insulin resistance, which can be employed as adjunctive therapy in type 2 DM.